Effects of white noise on off‐task behavior and academic responding for children with ADHD. Issue 1 (23rd September 2013) - Cook, Andrew; Bradley‐Johnson, Sharon; Johnson, C. Merle
<x xml:space="preserve">Abstract</x> We evaluated the effects of white noise played through headphones on off‐task behavior, percentage of items completed, and percentage of items completed correctly for 3 students with attention deficit hyperactivity disorder (ADHD). Headphones plus white noise were associated with decreases in off‐task behavior relative to baseline and headphones‐only (no white noise) control conditions. Little change in academic responding occurred across conditions for all participants.